Use of mutant mcm strain in purification of Neurospora crassa transformants resistant to hygromycin - Kamal Dev; Ramesh Maheshwari (Fungal Genetics Reports, 2001)
DNA-mediated transformation in Neurospora crassa results in the formation of heterokaryons comprising a mixture of both transformed and untransformed nuclei. This makes it imperative to resolve the transformed nuclei from the untransformed ones. The present methods for purifying the transformed nuclei from primary transformants include repeated plating of macroconidial transformant to enrich the transformed nuclei or producing uninucleate microconidia. Both these methods are labour intensive and time consuming. We report here a simple and efficient method of purifying the transformed nuclei by the induction of microconidiation in an otherwise non-microconidiating strain using a mcm mutant strain.